Experimental evidence for magnetic field effects on dielectronic recombination via high Rydberg states - Bartsch, Thomas; Schippers, S.; Müller, A.; Brandau, C.; Gwinner, G.; Saghiri, Amir Ahmad; Beutelspacher, Michael; Grieser, Manfred; Schwalm, Dirk; Wolf, Andreas; Danared, H.; Dunn, G. H. (Physical review letters, 1999)
We report the first experimental observation of magnetic field effects on dielectronic recombination (DR) via highly excited Rydberg levels. Crossed static electric and magnetic fields Ey and Bz were imposed on the collision region in high resolution DR measurements with Li-like Cl14+ ions at the heavy ion storage ring TSR in Heidelberg. Enhancement of DR rate coefficients α for the group of high Rydberg states attached to the 2p1/2 and 2p3/2 series limits was observed when motional electric fields Ey up to 380 V/cm were introduced. The associated enhancement rate dα/dEy which we found to be constant at least for Ey≤100V/cm decreased by almost a factor of 2 when the longitudinal field Bz was increased from 20 to 69 mT.
Gesehen am 30.11.2020